Effect of Pyridyl Substitution on Chemical and Photochemical Water Oxidation by [Ru(terpyridine)(bipyridine)(OH2)]2+ Scaffolds. Issue 1 (19th December 2016) - Patel, Jully; Majee, Karunamay; Ahmad, Ejaz; Das, Babulal; Padhi, Sumanta Kumar
Abstract : The complexes [Ru(2‐py‐tpy)(bpy)(OH2 )][PF6 ]2 (1 ; bpy = 2, 2′‐bipyridine), [Ru(3‐py‐tpy)(bpy)(OH2 )][PF6 ]2 (2 ), and [Ru(4‐py‐tpy)(bpy)(OH2 )][PF6 ]2 (3 ; n ‐py‐tpy = 4′‐( n ‐pyridyl)‐2, 2′:6′, 2′′‐terpyridine, n = 2–4), as electronic modifications of the [Ru(tpy)(bpy)(OH2 )][PF6 ]2 scaffold, have been synthesized and characterized thoroughly by several spectroscopic methods. All three complexes were employed as catalysts for chemical and photochemical water oxidation. The free nitrogen atom of the pyridine ring in catalysts1 –3 is protonated at pH 1 and acts as an electron‐withdrawing group. For2, the meta ‐nitrogen atom has a larger withdrawing effect compared with those of1 and3, as the positive charge (δ+) is delocalized only at the carbon atoms. However, the positive charge (δ+) is distributed among the nitrogen and carbon atoms of the pyridine ring for the ortho ‐ and para ‐nitrogen atoms in1 and3, respectively. Electrochemical and manometry studies revealed that1 and3 are better catalysts owing to the weaker electron‐withdrawing effects than that for2 . All of these complexes also act as efficient catalysts towards the photo‐oxidation of water in pH 6.5 phosphate buffer at 20 °C in the presence of [Ru(bpy)3 ] 2+ as a photosensitizer and Na2 S2 O8 as a sacrificial electron acceptor. Abstract : Three mononuclear complexes [Ru( n ‐py‐tpy)(bpy)(OH2 )] 2+ ( n = 2–4, py = pyridyl, tpy = 2, 2′:6′, 2′′‐terpyridine, bpy = 2, 2′‐bipyridine) are synthesized, and their catalysis of water oxidation by chemical and photochemical methods is demonstrated. The electron‐withdrawing effect of the terminal pyridyl group plays a key role in the catalysis.